Shaping Teat Suction Forces of Liners with Varied Structure of Rubber Core (Agricultural Engineering, 2019)
A liner is the only part of the milking unit which has a direct contact with a cow’s teat. It ensures a correct circulation of body liquids in a teat with its suitable massage and creates conditions for a teat to open and milk to flow out and maintains a milking cup on a teat. The result of the last task is generation of a suction force that sucks a teat into a liner. During milking, when a cup is placed on a teat, counter forces are generated that try to remove a liner from a teat and forces that cause that a teat moves up to a liner producing a phenomenon of “a climbing cup”. Forces that tend to separate a teat from a liner depend on the mass of a milking cup set and the value of the friction force. A counter force that tends to suck a teat into a liner is proportional to the level of negative pressure in a liner and the surface of cross-section of a teat that is subjected to negative pressure. We should also assume that also the structure of a liner will influence this force. The paper presents results of the laboratory tests on the impact of the shape of the cross-section of a rubber core and construction solutions of liners on the vacuum force of a liner when a teat is sucked into a teat chamber. Eight liners, popular in milking machines used in our country were used in the tests. Various penetrations of a teat (50, 62, 75 and 100 mm), working pressure (25-55 kPa) and a working stage of the milking cup were additional variables. In order to determine whether and what is the degree of the impact of variability sources on shaping the suction forces of a liner, a static processing of results was carried out using a multi-variance analysis. It was proved that at the significance level of α=0.05, the source of variability assumed in the experiment in the form of the liner shape, negative pressure and penetration affected the analysed sizes, i.e. Average values of suction forces in the suction phase (Fws) and massage phase (Fwm). The investigation of the impact of the rubber core part on the determined values of the suction force in the function of variable negative pressure proved that at teat penetration of 50 and 62 mm (the most popular lengths of teats in milked cows), the lowest suction force was observed in case of a liner with a triangular cross-section, slightly bigger with a square cross-section and the highest suction force is generated by round and oval liners.